EFEITO DA PEÇONHA DE Tityus confluens BORELLI, 1899 (BUTHIDAE) SOBRE A ATIVIDADE DE ENZIMAS DO SISTEMA PURINÉRGICO DE LINFÓCITOS E PLAQUETAS DE RATOS - Romario da Silva Portilho (2024)
Purinergic signaling pathways play crucial roles in regulating hemostatic and inflammatory responses, both of which are impacted by scorpion envenomation. Scorpion venoms are complex mixtures containing various toxins such as peptides, enzymes, and nucleotides. Previous studies have highlighted the influence of scorpion venom toxins on purinergic signaling, including purinergic receptors, and have identified putative ectonucleotidases within venom compositions. This study aimed to investigate the capacity of Tityus confluens scorpion venom (10, 50 and 100 μg/mL) to metabolize adenine nucleotides and its potential effects on purinergic enzyme activity in rat blood cells, specifically platelets and lymphocytes. The effects of T. confluens venom on the activity of E-NTPDase (ATP and ADP hydrolysis), E-5’-NT (AMP hydrolysis), and E-ADA (ADO hydrolysis) were analyzed. Results revealed that crude venom from T. confluens exhibited ATP nucleotide hydrolysis activity across all tested concentrations. In lymphocytes, ADP hydrolysis was inhibited at 100 μg/mL, while ADO hydrolysis was increased across all concentrations of venom. In platelets, ATP hydrolysis was inhibited at 100 μg/mL of venom, whereas AMP and ADO hydrolysis were inhibited across all concentrations. When considering these findings collectively, the data suggests an elevation in extracellular ATP levels and a reduction in extracellular ADO, aligning with clinical manifestations of envenomation characterized by a proinflammatory milieu. This study underscores the intrinsic ATPase activity of T. confluens venom and its ability to modulate the activity of E-NTPDase, E-5’-NT, and E-ADA in rat blood cells.